Proceedings of the 15th New Zealand Conference on Human-Computer Interaction 2015
DOI: 10.1145/2808047.2808055
|View full text |Cite
|
Sign up to set email alerts
|

Reading text in an immersive head-mounted display

Abstract: This paper describes an experiment conducted as part of a larger project investigating the possibilities of using a virtual environment for users performing day-to-day computing tasks. The experiment is a user study analyzing the performance of reading tasks typical of a general purpose computing environment conducted in immersive virtual reality headsets. Results of this study are evaluated, and suggest that reading tasks can be performed with near equivalent performance in the virtual environment when compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(2 citation statements)
references
References 8 publications
0
0
0
Order By: Relevance
“…Studies have explored issues with readability in Mixed Reality (MR) environments. While reading in virtual monitors has been shown to be feasible (Grout et al, 2015;Pavanatto et al, 2021), large flat monitors were reported to impair readability (Grout et al, 2015). It has been suggested that text displayed on virtual elements should be displayed larger than on physical monitors (Dittrich et al, 2013;Pavanatto et al, 2021), although that can lead to reduced performance due to small FOVs (Pavanatto et al, 2021).…”
Section: Readability In Mixed Realitymentioning
confidence: 99%
“…Studies have explored issues with readability in Mixed Reality (MR) environments. While reading in virtual monitors has been shown to be feasible (Grout et al, 2015;Pavanatto et al, 2021), large flat monitors were reported to impair readability (Grout et al, 2015). It has been suggested that text displayed on virtual elements should be displayed larger than on physical monitors (Dittrich et al, 2013;Pavanatto et al, 2021), although that can lead to reduced performance due to small FOVs (Pavanatto et al, 2021).…”
Section: Readability In Mixed Realitymentioning
confidence: 99%
“…Previous work investigated various visual attributes of text presentation in virtual environments. Conducting a study about presenting desktop interfaces inside an immersive virtual environment, Grout et al [15] showed that users can achieve traditional reading tasks in an immersive virtual environment with a near-real-world performance. Comparing diferent output media, Dittrich et al [11] suggest that text in a 3D virtual environment should be displayed larger than on a 2D display.…”
Section: Text Presentation and Location In Virtual Environmentsmentioning
confidence: 99%